Forest and water policy integration: A process and output-oriented policy network analysis - Eulàlia Baulenas; Sylvia Kruse; Metodi Sotirov (Environmental Policy and Governance, 2021)
Natural resource management requires cross-sectoral policy integration because the scope of current environmental and sustainability issues surpasses traditional sectoral boundaries. While the emergence of policy networks in such cases has been observed in the policy integration literature, little is known about how these networks are formed and how they influence the processes and outputs of policy integration. Accordingly, the main aim of this article is to combine the policy integration and policy network literatures to answer two research questions: How can the formation of a policy network for the case of forest and water policy integration be explained? What are the effects of the policy network on policy integration outputs? We use qualitative interviews and social network analysis to inform the study of two regional case studies in Germany and Spain. Our results show the relevance of a policy broker in steering the interactions between forest and water policy actors, combined with the presence of synergetic interdependencies, which facilitated the activation of the network. Additionally, the activities performed contributed to ideational homogenization between the forest and water sectors in terms of problem definition and preferred solutions, despite initial divergences. We conclude that a policy network perspective is an important contribution to the policy integration literature because it allows differentiating the influence of actor-level and network-level factors on integrated processes and outputs. In conclusion, both actors and their relationships should be accounted for as key intermediary variables to better understand and steer policy integration between natural resource sectors.
Keywords: 330; interdependencies; forest; Germany; policy actors; policy integration; policy network; Spain; subnational policy; water